Retapamulin: focus on its use in the treatment of uncomplicated superficial skin infections and impetigo. (October 2010) - Jacobs, Michael R
Staphylococcus aureus and Streptococcus pyogenes are the predominant bacterial pathogens associated with uncomplicated superficial skin infections and impetigo. Treatment of these infections has been compromised by the development of antimicrobial resistance, including resistance to β-lactams ('methicillin' resistance), fluoroquinolones, macrolides, clindamycin and mupirocin in S. aureus, and to macrolides and clindamycin in S. pyogenes . Retapamulin is a semisynthetic antimicrobial agent belonging to the pleuromutilin class, which prevents protein synthesis in bacteria via a unique mode of action. This agent has in vitro activity against staphylococci and streptococci resistant to other classes of agents, including methicillin-resistant S. aureus, and has a low potential for the development of mutational resistance. Over 3000 patients were studied in clinical trials of retapamulin, which is now the first pleuromutilin introduced into human use as a topical agent for the treatment of skin and skin structure infections such as impetigo, secondarily infected dermatoses and secondarily infected traumatic lesions.